Herpes simplex virus amplicon: effect of size on replication of constructed defective genomes containing eucaryotic DNA sequences. - Kwong, A D (1984)
Previous studies (R. R. Spaete and N. Frenkel, Cell 30:295-304, 1982) have documented the potential use of defective virus vectors (amplicons) derived from herpes simplex virus for the efficient introduction of foreign DNA sequences into eucaryotic cells. Specifically, cotransfection of cells with helper virus DNA and cloned amplicons (8 to 10 kilobases [kb]) containing bacterial plasmid DNA sequences linked to a set of herpes simplex virus cis-acting propagation signals (a replication origin and a cleavage-packaging signal) resulted in the generation of virus stocks containing packaged defective genomes that consisted of uniform head-to-tail reiterations of the chimeric seed amplicon sequences. The chimeric defective genomes could be stably propagated in virus stocks and could thus be used to efficiently infect cells. We now report on additional studies designed to propagate relatively large sets of eucaryotic DNA sequences within chimeric packaged defective genomes. These studies have utilized a 12-kb chicken DNA sequence encoding the chicken ovalbumin gene and cloned by Lai et al. (Proc. Natl. Acad. Sci. U.S.A. 77:244-248, 1980) in the plasmid pOV12. Virus stocks derived from cells cotransfected with helper virus DNA and chimeric amplicons (overall size of 19.8 kb, of which 12 kb corresponded to the chicken DNA) contained defective genomes composed of reiterations of the 19.8-kb seed amplicon sequences. However, in addition to the authentically sized repeat units, defective genomes in the derivative virus stocks contained smaller repeat units representing deleted versions of the seed 19.8-kb amplicons. The recombinational events leading to the formation of deleted repeats did not appear to occur at unique sites, as shown by comparative analyses of multiple, independently generated virus series propagated from separate transfections. In contast, seed amplicons ranging in size from 11 to 15 kb and containing subsets of the 12-kb chicken DNA sequences replicated efficiently and could be stably propagated in virus stocks. The results of these studies suggest the existence of size restrictions (up to 15 kb) on the efficient replication of seed herpes simplex virus amplicons.